FORMATION OF PROFESSIONAL COMPETENCE IN MEDICAL STUDENTS: THE ROLE AND IMPORTANCE OF PEDAGOGY AND PSYCHOLOGY - Tajiboyeva Odinakhon; Unarboyev Javlon (TADQIQOTLAR, 2025)
Abstract: This article provides a scientific analysis of the interrelation, integration, and significance of pedagogy and psychology in the process of developing professional competence among medical students in higher medical education institutions. It explores the essence and structure of professional competence, as well as the formation of empathy, reflection, and communication skills in the personality of a future physician.